Is There a Right to Have Rights? The Case of the Right of Asylum - Heuser, Stefan (Ethical theory and moral practice, 2008)
In dialogue with the political philosophy of Hannah Arendt and Seyla Benhabib the author draws on the idea of a right to have rights and raises the question under which political conditions asylum can be a subjective right for political refugees. He argues that mere spontaneous acts of humanitarianism will not suffice to define the institutional commitments of liberal democracies in refugee policy. At the same time, no duty for any particular state to take up refugees can be derived from a right to have rights. The quest for institutional solutions for a timely migration and asylum policy will rather enhance the discourses on the self-understanding of liberal democracies. With a critical eye on German asylum legislation and legal practice, the author contends that it will be a task of any co-ordinated European right of asylum to define political persecution in relation to the first dimension of human rights in order to differentiate the right of asylum from immigration legislation.